Refractory response to entrectinib for ROS‐1 rearranged NSCLC with concurrent de novo TP53 mutation showing good response to CNS lesion, but poor duration of response: A case report - Kentaro Ito; Miho Nishio; Kentaro Fujiwara; Yoichi Nishii; Kengo Ushiro; Hiroki Yasui; Osamu Hataji (Thoracic Cancer, 2023)
Abstract Entrectinib, a ROS‐1 inhibitor, has been shown to be effective for patients with ROS‐1 fused NSCLC, and has been established as the standard of care for this population. Entrectinib has been shown to achieve a better response to brain metastasis due to the characteristic of the drug having a weak interaction with P‐glycoprotein and, even in prospective studies, the intracranial response is higher. Patients have been known to acquire resistance to molecularly targeted drugs such as EGF‐TKIs or ALK‐TKIs during targeted therapy. Similarly, the mechanisms of resistance to entrectinib have been reported, but information about the effects of TP53 mutation with entrectinib are still limited. Here, we experienced a case of a patient with ROS‐1 fusion and concurrent TP53 mutation who was treated with entrectinib, resulting in a response to brain metastasis but rapid resistance to entrectinib. Our case demonstrates both the intracranial activity of entrectinib and the potential for resistance to entrectinib due to TP53 mutation.